The application of theory of planned behaviour in pedestrian safety: a literature approach - Muhamad Nazri Borhan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Road accidents among pedestrian become an important issue that needs to be mitigated due to high injuries and fatalities cases. Pedestrian is a weakest group of people compared to the drivers because they are not fully protected. The accidents involving pedestrian may occur due to their own negative crossing behaviour. This study is purposely to identify the effectiveness of theory of planned behaviour (TPB) in predicting pedestrian behaviour. TPB has three main constructs which are attitudes, subjective norms and perceived behavioural control that significant to behavioural intention. Some studies used extended TPB by adding other constructs such as moral norms, perceived risk, conformity tendency, perceived severity, and past behaviour to predict pedestrian behaviour more accurately. This study used a literature approach where some of the previous studies are examined and the results of the studies are being analysed using descriptive analysis. The results show that TPB is suitable to predict pedestrian behaviour because the constructs are significant and comply with its fit. This study also shows that pedestrian behaviours are differ according to their age and gender. Most of previous studied states that young people tends to perform risky behaviours compared to old people. Children pedestrian are more vulnerable and have a high tendency to involve in road accidents and have a high fatality risk. Men are more risk-taking compared to women and men have high tendency to violate road regulations and exposed to injuries and fatality while women have more positive crossing behaviour.